The role of social influence in mediating the relationship between relative advantage and purchase intentions for smartphones: A study in Kathmandu, Nepal - Shrestha, Sajeeb Kumar; Karki, Tej Bahadur; Mahat, Dipak; Neupane, Dasarath (International Journal of Management and Sustainability, 2024)
This research explores smartphone usage dynamics in Kathmandu, Nepal, focusing on how relative advantage, social influence, and purchase intention interact in the context of the city’s growing technological landscape. To address the identified gap in understanding the mediating role of social influence, descriptive and exploratory research methods are used. A survey involving 412 smartphone users was conducted both in person and online. The study reveals that relative advantage significantly impacts both social influence and purchase intention. Social influence is found to partially mediate the relationship between relative advantage and purchase intention. Specifically, individuals who perceive a greater relative advantage in a smartphone, thereby further enhancing their purchase intention. The research provides valuable insights into the factors driving consumer behavior in Kathmandu’s smartphone market. It demonstrates that while relative advantage directly affects purchase intentions, social influence also plays a critical role in mediating this relationship. These findings can guide marketers in refining their product placement, promotional strategies, and community engagement efforts, ensuring they address both the perceived advantages of smartphones and the influence of social factors on consumer decisions.